Prevalence and Outcome of Preterm Neonates Admitted to Neonatal Unit of a Tertiary Care Center in Western Nepal - Paudel, Laxman; Kalakheti, Balkrishna; Sharma, Kiran (Journal of Lumbini Medical College, 2018)
Introduction: Preterm deliveries contribute to major morbidity and mortality in developing countries. They are a leading cause of admission in neonatal care units. Advances in the management have ensured better survival of preterm births, however cost, care and resource limitations influence the outcome.This study was conducted to determine the prevalence, risk factors, morbidity patterns and outcome of preterm admissions to a neonatal unit of a tertiary care center. Methods: This was a retrospective study where all preterm admissions over a period of two years were evaluated for maternal risk factors and morbidity pattern. Outcome was measured in terms of survival rate and case fatality rate. Mann Whitney U test and Fisher's Exact test were used to see the association between various parameters and clinical outcome. Results: Preterm admissions constituted16.48% of all neonatal unit admissions with a male to female ratio of 1.32:1. Common risk factors for preterm births were Prelabour Rupture of Membrane (31.2%) followed by Hypertensive Disorders in Pregnancy (15.1%) and Antepartum Hemorrhage (8.6%). Common morbidities were Sepsis (40.9%), Jaundice (28%) and Respiratory Distress Syndrome (RDS) (14%). Case fatality rate was significantly high in RDS (45.1%) and perinatal asphyxia (11.1%). Overall survival rate was 75.26%. Conclusion: Preterm births were an important cause for admissions in neonatal unit. Sepsis, jaundice, RDS and necrotizing enterocolitis were common morbidities observed. Since clinical outcome was related to gestational age, improving antenatal care, timely interventions and early referral of high risk pregnancies to tertiary level centers might improve the survival rate. DOI: https://doi.org/10.22502/jlmc.v6i2.218